Factors Related To Anxiety Level In The Elderly In The Time Of The Covid 19 Pandemic In Elderly Posyandu Lelateng Village - Kusumaningtiyas, Dwi Prima Hanis (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aimed to determine the factors that influence the level of anxiety in the elderly during the Covid-19 pandemic. The study was conducted in November 2020. The research design was descriptive-analytic, with a total sampling technique of sampling. The total population in this study was 62 elderly. The data collection technique used was a guided interview using a Self Reporting Questionnaire (SRQ-20) consisting of 20 question items. Data analysis in this research is a univariate analysis using frequency distribution analysis. And bivariate analysis using the chi-square test. The relationship between gender and anxiety levels were obtained with a value of p=0.601 (p<0.05). The relationship between age and level of anxiety was obtained p-value = 0.655 (p <0.05). The relationship between the disease and the level of anxiety obtained p-value = 0.876 (p < 0.05) The relationship between knowledge and anxiety level obtained p-value = 0.008 (p < 0.05)